KUALITAS LAYANAN DITINJAU DARI KOHESIVITAS KELOMPOK, EMPLOYEE EMPOWERMENT, DAN KEADILAN ORGANISASIONAL - Ni Luh Putu Ayu Reonningrat; Ni Luh Sili Antari (STIMI Handayani Denpasar, 2017)
Quality of service is a key factor in the success of a company that is engaged in services such as salons, hospitals, banks, and hotels. The banking industry is one that is always faced with intense competition and business environment changes so quickly. Currently the bank is not only required to understand its clients, but also should pay attention to their employees so that the company afloat by purpose. As one of the state-owned enterprises, Bank BRI is required to provide good service to its customers. Competition is going on and the number of privately owned banks that have sprung up to make BRI had to work extra hard in order not to drown in the competition in the financial sector. In this regard, it will be analyzed in this study about the influence of several variables on the quality of service. This research was conducted in BRI Unit Singaraja spread over 15 locations with the number of employees as a sample of 81 people. The results of this study indicate there is positive and significant between group cohesiveness on the quality of service, there is a positive and significant impact of employee empowerment on service quality, there is positive but not significant between justice organizational to quality of service, there is a positive and significant impact group cohesiveness, employee empowerment, and organizational justice to the quality of the service employees of BRI in Singaraja, as well as the effect of which was donated by three independent variables on the quality of service of 77.5%.